PERCEIVED ENVIRONMENTAL UNCERTAINTY AND INNOVATION ADOPTION: EXPLORING THE TURKISH CONTEXT - (:unkn) unknown (My University, 2019)
Because innovation and environmental uncertainty are highly crucial concepts for organizations’survival, and managers are key decision makers in organizational operations, investigating the relationshipbetween innovation and environmental uncertainty from managers’ lenses is important. This study aims to explorehow managers’ adoption of radical and incremental innovation is affected by perceived environmental uncertainty(PEU). Data collected from 230 managers that work for companies that operate in various industries has beenanalyzed by using Multinomial logistic regression analysis. Results of the study indicate that government andpolicies factor is the effective factor on managers’ decisions on innovation adoption, and in uncertainenvironments in terms of governmental and policy factor, managers choose to adopt both types of innovation sincethey want avoid to take risks of adopting solely one type of innovation.

İnovasyon ve çevresel belirsizlik kuruluşların hayatta kalması için son derece önemli kavramlar_x000D_ olduğundan ve yöneticiler örgütsel operasyonlarda kilit karar vericiler olduğundan, yöneticilerin merceklerinden_x000D_ inovasyon ve çevresel belirsizlik arasındaki ilişkiyi araştırmak önemlidir. Bu çalışma, yöneticilerin radikal ve_x000D_ artımsal inovasyonu benimsemelerinin çevresel belirsizlikten (PEU) nasıl etkilendiğini araştırmayı_x000D_ amaçlamaktadır. Çeşitli sektörlerde faaliyet gösteren şirketlerde çalışan 230 yöneticiden toplanan veriler,_x000D_ Multinomial lojistik regresyon analizi kullanılarak analiz edilmiştir. Sonuçlar, hükümet ve politikalar faktörünün_x000D_ yöneticilerin inovasyonun benimsenmesine ilişkin kararları üzerinde etkili bir faktör olduğunu ve belirsiz_x000D_ ortamlarda, ‘devlet ve politika faktörü açısından’, yöneticilerin yalnızca bir yenilik türünü benimsemenin riskini_x000D_ almaktan kaçındıkları için her iki yeniliği benimsemeyi tercih ettiklerini göstermektedir.
ALGILANAN ÇEVRESEL BELİRSİZLİK VE İNOVASYONU BENİMSEME: TÜRKİYE BAĞLAMINI KEŞFETME
Keywords: İşletme Finans; İşletme